Participation of A. A. Dmitrievsky in the arrangement of church service at Leningrad Theological seminary - Sergey Akishin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article presents results of the study of archival fi les from A. A. Dmitrievsky’s series (Manuscript Department, National Library of Russia) which contain a number of records related to the history of Leningrad Theological Seminary. These records refl ect the fact that on October 18 (Memory day of the Four Holy Hierarchs of Moscow) and December 13 (Memory day of Apostle Andrew) 1926, four public church services in the name of Hieromartyr Isidore of Yurievsk took place with the help of the prominent scientist and liturgist A. A. Dmitrievsky at the Russian-Estonian church in Leningrad. Both the public church services and their preparation were probably employed by A. A. Dmitrievsky as a medium for achieving better results of his students in the process of liturgical study. It was the intention of students of the Theological Seminary and Higher Theological Courses to conduct these public services. A number of manuals were prepared for various categories of participants of the services (clergy, readers, choristers and laymen) in order to conduct the service according to liturgical books. Each of these manuals explained what had to be done at certain moments of the service, who had to interact with each other, etc. The general course of the service was determined by a specifi cally designed document “The Order of Public Worship”, which listed the elements of the service from start to fi nish. These documents are published in modern orthography as a supplement to this article.